Does your job really matter? Job-specific cancer incidence among a cohort coal mine workers in Queensland, Australia - Deborah Catherine Glass; Stella May Gwini; Anthony Del Monaco; Lin Fritschi; Michael J. Abramson; Malcolm Ross Sim; Karen Walker-Bone (International Archives of Occupational and Environmental Health, 2026)
Purpose Globally, coal production exposes millions of workers to coal mine dust. This study aimed to measure overall and site specific cancer incidence among coal mine workers (CMW) who performed different types of work. Methods A retrospective cohort of CMW in Queensland, Australia, was assembled using health assessment records from 1992. CMW were grouped by job type and then into Work Categories and linked to the Australian Cancer Database up to 2016. Standardized cancer incidence ratios (SIR) and relative cancer incidence ratios (aRIR) within the cohort, adjusted for age, era, and smoking status, were calculated for men and women with Poisson regression. Results There were 5,568 cancers diagnosed among 146,553 men and 396 in 19,927 women. The overall cancer risk was comparable to that of the general population for most Work Categories. The risk of lung cancer was higher for male Production (SIR 123, 95% Confidence Interval [CI] 107–142; adjusted Relative incidence Ratio (aRIR) (adjusted for era, age and smoking status) 1.23, 95%CI 0.99-1.52) and Construction workers (SIR 189, 95%CI 31–272; aRIR 1.78, 95%CI 1.20–2.62) when compared with the Australian population and within the cohort after adjusting for smoking. Laryngeal cancer was increased in Production workers (SIR 145, 95%CI 100–212). Conclusions Increased rates of lung and laryngeal cancers were identified for male Production workers and lung cancer for Construction workers. These could be related to mine workplace exposures such as silica and diesel engine exhaust.

Longitudinal measurements of per- and poly-fluoroalkyl substances (PFAS) in archived human serum samples between 1975 and 1995 in Australia - Sandra Nilsson; Jennifer Bräunig; Renee N. Carey; Jennie Hui; Kayla Smurthwaite; Leisa-Maree Toms; Martyn D. Kirk; Jochen F. Mueller; Lin Fritschi (Journal of Hazardous Materials, 2023)

Lifetime recreational physical activity and the risk of prostate cancer - Elizabeth Sorial; Si Si; Lin Fritschi; Ellie Darcey; Justine E. Leavy; Jennifer Girschik; Gina L. Ambrosini; Terry Boyle (Cancer Causes & Control, 2019)

Nonsteroidal anti-inflammatory drugs, statins, and pancreatic cancer risk: a population-based case–control study - Pik Fang Kho; Jonathan Fawcett; Lin Fritschi; Harvey Risch; Penelope M. Webb; David C. Whiteman; Rachel E. Neale (Cancer Causes & Control, 2016)

Home paint exposures and risk of childhood acute lymphoblastic leukemia: findings from the Childhood Leukemia International Consortium - Helen D. Bailey; Catherine Metayer; Elizabeth Milne; Eleni Th. Petridou; Claire Infante-Rivard; Logan G. Spector; Jacqueline Clavel; John D. Dockerty; Luoping Zhang; Bruce K. Armstrong; Jérémie Rudant; Lin Fritschi; et al. (Cancer Causes & Control, 2015)

Association between Helicobacter pylori and pancreatic cancer risk: a meta-analysis - Annaka Schulte; Nirmala Pandeya; Jonathan Fawcett; Lin Fritschi; Harvey A. Risch; Penelope M. Webb; David C. Whiteman; Rachel E. Neale (Cancer Causes & Control, 2015)

Smoking, alcohol, diabetes, obesity, socioeconomic status, and the risk of colorectal cancer in a population-based case–control study - Terry Boyle; Lin Fritschi; Seyed Mehdi Tabatabaei; Kathrin Ringwald; Jane S. Heyworth (Cancer Causes & Control, 2014)

Parental occupational paint exposure and risk of childhood leukemia in the offspring: findings from the Childhood Leukemia International Consortium - Helen D. Bailey; Lin Fritschi; Catherine Metayer; Claire Infante-Rivard; Corrado Magnani; Eleni Petridou; Eve Roman; Logan G. Spector; Peter Kaatsch; Jacqueline Clavel; Elizabeth Milne; John D. Dockerty; et al. (Cancer Causes & Control, 2014)

Erratum to: Exposure to pesticides and the risk of childhood brain tumors - Kathryn R. Greenop; Susan Peters; Helen D. Bailey; Lin Fritschi; John Attia; Rodney J. Scott; Deborah C. Glass; Nicholas H. de Klerk; Frank Alvaro; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2014)

Erratum to: Exposure to household painting and floor treatments, and parental occupational paint exposure and risk of childhood brain tumors: results from an Australian case–control study - Kathryn R. Greenop; Susan Peters; Lin Fritschi; Deborah C. Glass; Lesley J. Ashton; Helen D. Bailey; Rodney J. Scott; John Daubenton; Nicholas H. de Klerk; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2014)

Childhood and parental diagnostic radiological procedures and risk of childhood brain tumors - Elizabeth Milne; Kathryn R. Greenop; Lin Fritschi; John Attia; Helen D. Bailey; Rodney J. Scott; Lesley J. Ashton; Elizabeth Smibert; Bruce K. Armstrong (Cancer Causes & Control, 2014)

Exposure to household painting and floor treatments, and parental occupational paint exposure and risk of childhood brain tumors: results from an Australian case–control study - Kathryn R. Greenop; Susan Peters; Lin Fritschi; Deborah C. Glass; Lesley J. Ashton; Helen D. Bailey; Rodney J. Scott; John Daubenton; Nicholas H. de Klerk; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2014)

Exposure to pesticides and the risk of childhood brain tumors - Kathryn R. Greenop; Susan Peters; Helen D. Bailey; Lin Fritschi; John Attia; Rodney J. Scott; Deborah C. Glass; Nicholas H. de Klerk; Frank Alvaro; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2013)

Quantitative exposure metrics for sleep disturbance and their association with breast cancer risk - Jennifer Girschik; Lin Fritschi; Thomas C. Erren; Jane Heyworth (Cancer Causes & Control, 2013)

Resistance training and the risk of colon and rectal cancers - Terry Boyle; Fiona Bull; Lin Fritschi; Jane Heyworth (Cancer Causes & Control, 2012)

Timing and intensity of recreational physical activity and the risk of subsite-specific colorectal cancer - Terry Boyle; Jane Heyworth; Fiona Bull; Sarah McKerracher; Cameron Platell; Lin Fritschi (Cancer Causes & Control, 2011)

Parental occupational exposure to exhausts, solvents, glues and paints, and risk of childhood leukemia - Alison Reid; Deborah C. Glass; Helen D. Bailey; Elizabeth Milne; Bruce K. Armstrong; Frank Alvaro; Lin Fritschi (Cancer Causes & Control, 2011)

Non-cancer mortality among people diagnosed with lymphohaematopoietic neoplasm in Australia - Peter D. Baade; Jill A. Royle; David J. Joske; Lin Fritschi (Cancer Causes & Control, 2011)

Relationship between cardiopulmonary mortality and cancer risk and quantitative exposure to polycyclic aromatic hydrocarbons, fluorides, and dust in two prebake aluminum smelters - Melissa C. Friesen; Geza Benke; Anthony Del Monaco; Martine Dennekamp; Lin Fritschi; Nick de Klerk; Jan L. Hoving; Ewan MacFarlane; Malcolm R. Sim (Cancer Causes & Control, 2009)

Deaths from non-melanoma skin cancer in Western Australia - J. Girschik; Lin Fritschi; T. Threlfall; T. Slevin (Cancer Causes & Control, 2008)

The incidence of second primary invasive melanoma in Queensland, 1982–2003 - Kieran A. McCaul; Lin Fritschi; Peter Baade; Michael Coory (Cancer Causes & Control, 2008)

Trends in exposure of veterinarians to physical and chemical hazards and use of protection practices - Lin Fritschi; Adeleh Shirangi; Ian D. Robertson; Lesley M. Day (International Archives of Occupational and Environmental Health, 2007)

Occupational exposure to ionizing and non-ionizing radiation and risk of non-Hodgkin lymphoma - Ken K. Karipidis; Geza Benke; Malcolm R. Sim; Timo Kauppinen; Anne Kricker; Ann Maree Hughes; Andrew E. Grulich; Claire M. Vajdic; John Kaldor; Bruce Armstrong; Lin Fritschi (International Archives of Occupational and Environmental Health, 2007)

Health behaviors of cancer survivors: data from an Australian population-based survey - Elizabeth G. Eakin; Danny R. Youlden; Peter D. Baade; Sheleigh P. Lawler; Marina M. Reeves; Jane S. Heyworth; Lin Fritschi (Cancer Causes & Control, 2007)

Non-Cancer Mortality among People Diagnosed with Cancer (Australia) - Peter D. Baade; Lin Fritschi; Elizabeth G. Eakin (Cancer Causes & Control, 2006)

Risk of non-Hodgkin lymphoma associated with occupational exposure to solvents, metals, organic dusts and PCBs (Australia) - Lin Fritschi; Geza Benke; Ann M. Hughes; Anne Kricker; Claire M. Vajdic; Andrew Grulich; Jennifer Turner; Samuel Milliken; John Kaldor; Bruce K. Armstrong (Cancer Causes & Control, 2005)

Respiratory symptoms and lung-function changes with exposure to five substances in aluminium smelters - Lin Fritschi; Malcolm R. Sim; Andrew Forbes; Michael J. Abramson; Geza Benke; William A. Musk; Nicholas H. de Klerk (International Archives of Occupational and Environmental Health, 2003)

Animal-related occupations and the risk of leukemia, myeloma, and non-Hodgkin's lymphoma in Canada - Lin Fritschi; Kenneth C. Johnson; Erich V. Kliewer; Rick Fry (Cancer Causes & Control, 2002)

Respiratory symptoms and lung function in bauxite miners - Jeremy R. Beach; Nicholas H. de Klerk; Lin Fritschi; Malcolm R. Sim; A. William Musk; Geza Benke; Michael J. Abramson; John J. McNeil (International Archives of Occupational and Environmental Health, 2001)